Studies on Abundance of Jellyfish in Beach Seine Landings along the Coast of Greater Accra Region of Ghana - Adongo, P.A. (University of Ghana, 2019)
The study was conducted in three landing villages along the coast of Greater Accra Region of Ghana, namely; Ada, La and Bortianor from November 2018 to April 2019. The purpose of the study was to assess the abundance of jellyfish in beach seine landings. Biological data was obtained primarily from local fishermen who deployed beach seine net. The jellyfish families that were encountered were four in number and a total of 2,676 individuals from 72 beach seine hauls. These were; Catostylidae (35%), Chirodropidae (31%), Rhizostomatidae (30%) and Pelagiidae (4%). Ada had 37% of jellyfish, La 49% and Bortianor 14% of the total jellyfish landings. Rhizostomatidae was the most abundant at Ada, whereas Chirodropidae and Catostylidae were the most abundant at La and Bortianor respectively. The fish families that were encountered together with the jellyfish were thirteen and consisted of 352,228 individuals. They were; Carangidae > Portunidae > Penaeidae > Dasyatidae > Sciaenidae > Haemulidae > Cynoglossidae > Sphyraenidae > Sparidae > Stromateidae > Lutjanidae > Trichiuridae > Sepiidae; in order of decreasing abundance. Physico-chemical parameters at each site where fishing was carried out were collected. Five water quality parameters (DO, Conductivity, TDS, Phosphate and Chlorophyll-a) out of the eleven water parameters measured were identified to contribute significantly to the biological variations observed. A Canonical Correspondence Analysis (CCA) was used to identify which of the principal water quality parameters influenced abundance of both jellyfish and fish at each site. Decreasing DO, Conductivity and Chlorophyll-a levels influenced a decrease of jellyfish at Ada while increasing DO, Conductivity and Chlorophyll-a influenced an increase of jellyfish at La. Conversely, decreasing levels of TDS and Phosphate led to a decrease in Bortianor.
MPhil. Fisheries Science
Keywords: Jellyfish; Aurelia aurita; Aquaculture; Power Plants; Blooms Incidence; Fisheries